Effects of broccoli sprout supplements enriched in glucoraphanin on liver functions in healthy middle-aged adults with high-normal serum hepatic biomarkers: A randomized controlled trial - Satomi, Shohei; Takahashi, Shingo; Yoshida, Kazutaka; Shimizu, Sunao; Inoue, Takuro; Takara, Tsuyoshi; Suganuma, Hiroyuki (Frontiers in Nutrition, 2022)
Sulforaphane (SFN), an isothiocyanate derived from glucoraphanin, has antioxidant and anti-inflammatory effects that may be beneficial for improving liver function. However, few studies regarding the effects of glucoraphanin on the biological markers related to liver function, such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma-glutamyltransferase (γ-GTP) in healthy individuals have been reported. This randomized, double-blind, placebo-controlled parallel-group trial was conducted from April 22 to December 25, 2021 and compared the effects of broccoli sprout supplements enriched in glucoraphanin (glucoraphanin supplements) (n = 35) with those of placebo supplements (n = 35). This trial was registered with the University Hospital Medical Information Network Clinical Trial Registry (UMIN-CTR; ID number UMIN000044005) (https://center6.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000050252). Glucoraphanin significantly improved serum ALT levels at 24 weeks compared to placebo supplements. However, no significant difference in serum glutathione levels, one of the major antioxidants synthesized in the liver, was observed between the two groups. In conclusion, daily intake of the glucoraphanin supplements is beneficial for maintaining liver health in healthy, middle-aged adults with high-normal serum hepatic biomarkers, although further studies focusing on other antioxidant markers are needed to understand how glucoraphanin improves liver function.